CREATING PRIMARY KNOWLEDGE OF ENERGY IN PRIMARY CLASS STUDENTS - Raupova Sojida Abduvaitovna (Journal of Higher Education and Academic Advancement, 2024)
The article describes the methodical description of the formation of the initial concepts of energy in natural sciences in elementary school students, the development of various types of assignments.